Death on the Wards: Preparing Medical Students for Clinical and Clerical Duties - Katherine Anne Schultes; Norma Saks (Association of American Medical Colleges, 2012)
Abstract Introduction The aftermath of a patient's death is an emotional time for both the medical team and the patient's family and should be handled with the utmost professionalism. While most medical schools include instruction about death and dying, specific training on physician responsibilities after a patient's death is lacking. The purpose of this student-initiated project was to improve medical students' familiarity about what to do after a patient's death and increase confidence in carrying out these duties. Methods Workshop topics and activities were modified from those in residency training, including information about completing death certificates and communicating with families about autopsies, organ donation, and generally about the death of a loved one. Instruction included an interactive PowerPoint lecture, handouts, and individual and small-group activities (e.g., role-plays). Self-assessment tools include pre- and postworkshop questionnaires evaluating knowledge and confidence in performing physicians' tasks after a patient's death. Results The workshop was presented to 24 third-year medical students who evaluated the experience and faculty leadership regarding session format, content, quality of facilitator skills, and the usefulness of the workshop. Results showed significant improvement in knowledge about the clerical skills and confidence in performing these responsibilities after a patient's death. The most useful aspect of the workshop appeared to be role-play and death certificate exercises. Discussion Teaching medical students before they enter residency about the roles and responsibilities they will encounter after the death of a patient is crucial for a more favorable experience between the patient's family and the health care team.